Mechanical circulatory support in cardiogenic shock and post-myocardial infarction mechanical complications - Rob, Daniel; Bělohlávek, Jan (Journal of geriatric cardiology, 2022)
Despite advanced therapies, the mortality of patients with myocardial infarction (MI) complicated by cardiogenic shock (CS) remains around 50%. Mechanical complications of MI are rare nowadays but associated with high mortality in patients who present with CS. Different treatment strategies and mechanical circulatory support (MCS) devices have been increasingly used to improve the grim prognosis of refractory CS. This article discusses current evidence regarding the use of MCS in MI complicated by CS, ventricular septal rupture, free wall rupture and acute mitral regurgitation. Device selection should be tailored according to the cause and severity of CS. Early MCS initiation and multidisciplinary team cooperation is mandatory for good results. MCS associated bleeding remains a major complication and an obstacle to better outcomes. Ongoing prospective randomized trials will improve current knowledge regarding MCS indications, timing, and patient selection in the coming years.